Microstructure evolution in bulk and surface states of chromium rich nickel based cast alloys reinforced by hafnium carbides after exposure to high temperature air. (August 2014) - Berthod, P.; Conrath, E.
<x content-type="archive" xml:space="preserve">Abstract</x> Three alloys based on nickel, with a high level of chromium (25 wt-%) and containing varied quantities of carbon, 0·25 and 0·50 wt-%, and hafnium, 3·7 and 5·6 wt-%, fabricated by casting, were subjected to a 46 h long exposure at 1200°C in dry industrial air. The aim of the work was to investigate the thermal stability of their carbide interdendritic network and to discover their general behaviour in high temperature oxidation. The volume fraction of the hafnium carbides decreased slightly during high temperature exposure but their fragmentation was rather limited. In contrast, chromium carbides appeared in the two alloys, which initially contained exclusively HfC, and this may result in a decrease in their high temperature properties. The evolution of the carbides appeared to be responsible for a moderate lowering of room temperature hardness. The behaviour of the three alloys during high temperature oxidation was very good, despite the unusually high content of hafnium. All were chromia-forming, although oxidation of Hf led to HfO2 islands in the external scale and in the subsurface region. In summary, the behaviour of these three alloys showed that the HfC containing Ni–25Cr family is potentially interesting for applications at very high temperatures.